Bare morphology - Villalva, Alina (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
Several cases of Portuguese words that share the same root string are studied, representing different types of conversion. Such is the case with firmADJ – firmarV; abaixADV – abaixarV; manchN – mancharV; afiaV – afiaN. In order to set them apart one needs to take into account features from every grammar domain. It may be concluded that this fact is one of the best arguments for considering conversion as a lexical word formation process (as opposed to morphological, syntactic or semantic notions).